THE FIRST SETTLEMENTS OF FOOTHILLS AND FOOTHILL PLAIN OF ZAGROS: A GENERAL OVERVIEW - Amirov, Sahmardan Nazimovic (History, Archeology and Ethnography of the Caucasus, 2022)
In the article a general overview of the first Pre-Pottery Neolithic settlements of the Zagros foothills zone of primary domestication is presented. The inner Zagros area, at an altitude of more than 1000 m above sea level, is the zone of the natural habitation of the wild ancestors of cultivated plants and small ungulates. In this area there are known long-term settlements of the earliest Pre-Pottery Neolithic stage, where the formation of a productive economy is documented. These settlements are dated from the second half of X-IX millennium BC. At the same time, the foothills of the Zagros are outside the natural habitat of the ancestors of cultivated plants and domestic animals. The earliest sedentary settlements in this part of the Zagros Mountains represent the Late Pre-Pottery Neolithic stage, and are dated to the second half of the VIII millennium BC. These settlements were investigated in different natural-ecological zones - from foothill-steppe landscapes to the border with the alluvial plain of Southern Mesopotamia. At the same time, all the early Neolithic settlements of the Zagros foothills are placed in the zone of risky farming, insufficient to produce a sustainable crop in the modern conditions. This fact suggests that at the time of the initial human settlement, the humidity in this part of the Mesopotamian Lowlands was much greater than at present. The time of the primary sedentary development of the Zagros foothills and foothill plain coincides with the period of climatic optimum of the second half of the VIII millennium BC., which is currently traced both in the western and eastern parts of the Levantine-Mesopotamian lowlands. The finale of the Pre-Potery Neolithic settlements in the Zagros foothills can be associated with an exceptionally arid and sufficiently extended cycle dated from the end of VIII-VII millennium BC.
Keywords: Mesopotamian Plain; Zagros; Pre-Pottery Neolithic; settled lifestyle; domestication of plants and animals